Long-Term Effects of Phased Implementation of Antimicrobial Stewardship in Academic ICUs: 2007–2015*. Issue 2 (February 2019) - Morris, Andrew M.; Bai, Anthony; Burry, Lisa; Dresser, Linda D.; Ferguson, Niall D.; Lapinsky, Stephen E.; Lazar, Neil M.; McIntyre, Mark; Matelski, John; Minnema, Brian; Mok, Katie; Nelson, Sandra; et al.
Abstract : Objectives: Antimicrobial stewardship is advocated to reduce antimicrobial resistance in ICUs by reducing unnecessary antimicrobial consumption. Evidence has been limited to short, single-center studies. We evaluated whether antimicrobial stewardship in ICUs could reduce antimicrobial consumption and costs. Design: We conducted a phased, multisite cohort study of a quality improvement initiative. Setting: Antimicrobial stewardship was implemented in four academic ICUs in Toronto, Canada beginning in February 2009 and ending in July 2012. Patients: All patients admitted to each ICU from January 1, 2007, to December 31, 2015, were included. Interventions: Antimicrobial stewardship was delivered using in-person coaching by pharmacists and physicians three to five times weekly, and supplemented with unit-based performance reports. Total monthly antimicrobial consumption (measured by defined daily doses/100 patient-days) and costs (Canadian dollars/100 patient-days) before and after antimicrobial stewardship implementation were measured. Measurements and Main Results: A total of 239, 123 patient-days (57, 195 patients) were analyzed, with 148, 832 patient-days following introduction of antimicrobial stewardship. Antibacterial use decreased from 120.90 to 110.50 defined daily dose/100 patient-days following introduction of antimicrobial stewardship (adjusted intervention effect –12.12 defined daily dose/100 patient-days; 95% CI, –16.75 to –7.49; p < 0.001) and total antifungal use decreased from 30.53 to 27.37 defined daily doses/100 patient-days (adjusted intervention effect –3.16 defined daily dose/100 patient-days; 95% CI, –8.33 to 0.04; p = 0.05). Monthly antimicrobial costs decreased from 3195.56 to 1998.59 (adjusted intervention effect –642.35; 95% CI, –905.85 to –378.84; p < 0.001) and total antifungal costs were unchanged from 1771.86 to 2027.54 (adjusted intervention effect –355.27; 95% CI, –837.88 to 127.33; p = 0.15). Mortality remained unchanged, with no consistent effects on antimicrobial resistance and candidemia. Conclusions: Antimicrobial stewardship in ICUs with coaching plus audit and feedback is associated with sustained improvements in antimicrobial consumption and cost. ICUs with high antimicrobial consumption or expenditure should consider implementing antimicrobial stewardship programs. Abstract : Supplemental Digital Content is available in the text.